Innovation districts: an investigation of the replication of the 22@ Barcelona's Model in Boston - Morisson, Arnault (2014)
In 2000, the city of Barcelona launched 22@ Barcelona, dubbed the innovation district. The city sees the project as a means to accelerate Barcelona’s transition toward the knowledge economy. Other cities around the world have since followed the example of Barcelona, building or planning to build their own innovation districts. Boston began to establish its innovation district in 2010. Cities’ ultimate goal for these initiatives is to become more innovative and thus more competitive. Innovative districts are different from technology parks in that they aim to respond to a new economic paradigm in which economic production flows back to cities. The 22@ Barcelona model involves theoretical designs regarding five layers of innovation: economics, urban planning, productive, innovative, and creative. The comparative approach between 22@ Barcelona and Boston’s Innovation District intends to highlight the similarities and differences between those two innovation districts as well as providing a framework to define innovation districts.